Bridging Epistemological Delinking and Language Sciences - Barrantes-Montero, Luis Guillermo (2021)
This paper aims to offer a reflection regarding the urgency that the sciences of language, and concomitantly the sciences of education, as they are conceived and articulated in the Latin American present, carry out a profound review of their main insights, with the purpose of assuming appropriate organizing principles according to the local reality. As a conclusion, some clues are suggested, taking into account the Epistemic Delinking that the Decolonial Theory raises, in order to generate a situated and committed knowledge, thanks to the diversity of knowledge that is currently available, as well as to promote an epistemic attitude in the training of teachers.